(untitled) (Faridpur Medical College Journal, 2018)
A patient of ischemic heart disease (IHD) with additional carotid artery stenosis (CAS) has been distinguished as a high risk group for both heart and cerebral inconveniences following surgical intervention. We aimed to review the outcome of concurrent carotid endarterectomy (CEA) and off-pump coronary bypass graft (OPCABG)in a patient undergoing surgical revascularization for IHD and CAS at our institute.In the vicinity of 2014 and 2016, fifteen patients experienced OPCABG and CEA associatively in a single Surgeon’s Practice. Six (40%) patients had a history of myocardial infarction (MI), four (26.66%) had unstable angina (USAP), and three (20%) had USAP together with MI, though two (13.33%) were asymptomatic. Nine (60%) patients demonstrated no neurological manifestations, three (20%) had transient ischemic assaults (TIAs), two (13.33%) experienced stroke, and 1 (6.66%) experienced both. Majority 7 (46.66%) patients had 75-90% carotid artery stenosis and 6(40%) patients experienced right though 8 (53.33%) experienced left CEA and only 1 (6.66%) had bilateral CEA. Five (33.33%) patients were found left main disease (>50% lesion) and 100% patients have had significant Left Anterior Descending (LAD) lesion in this study. Twelve (80%) patients show significant lesion in Right Coronary Artery (RCA) and ten (66.66%) patients had Obtuse marginal (OM) branch disease. CEA was performed before OPCABG in all cases. There were 15 patients (mean age 62.5±2.8 years; 80% were male), two (13.33%) had a perioperative stroke while one of them had TIAs (6.6%). Mean ICU stay was 36.6±4.5 h and patients were released in 10 days. There was no mortality in the early postoperative period and co-morbidity was less significant (6.6% myocardial ischemia, 13.33% atrial fibrillation, 6.66% TIA, 13.33% Stroke). There was 1 (6.66%) postoperative acute renal failure evidenced by raised serum creatinine level. Two (13.33%) patients showed respiratory complications; only 6.6% of them suffered from wound infection. A combined strategy by means of CEA with OPCABG is safe and savvy in view of the satisfactory consequences of morbidity and mortality rates and also short ICU and hospital stay status. Faridpur Med. Coll. J. Jan 2018;13(1): 2-7